Fathers' expectations and autism: A critical discourse analysis of paternal narratives - Yunianti, Elvi; Mulya, Teguh Wijaya; Nanik, Nanik (Universitas Islam Sultan Agung, 2025)
The unique characteristics of autism spectrum conditions present significant challenges for families. Existing research often focuses on mothers' experiences, leading to the underrepresentation of fathers' perspectives. This study aims to highlight the expectations and experiences of fathers raising children on the autism spectrum. Using critical discourse analysis (CDA), the research explored how power dynamics and societal ideologies shape fathers' lived experiences in raising children on the autism spectrum. The fathers' narratives reveal that inadequate support—such as lack of professionalism, limited access to services, and insufficient community involvement—indicates that society has yet to achieve true inclusivity. Additionally, fathers stress the importance of comprehensive support in managing their parenting responsibilities. The findings emphasize (1) the discourse on integrated support services and (2) addressing paternal support: insights from fathers' experiences. These results underscore the need to strengthen support systems for fathers of children on the autism spectrum.